A conceptual model to improve links between science, policy and practice in coastal management. (May 2019) - Dale, Pat; Sporne, Ilva; Knight, Jon; Sheaves, Marcus; Eslami-Andergoli, Leila; Dwyer, Patrick
Abstract: The literature has identified significant barriers to sustainable management of coastal resources due to lack of integration between science, policy and practice. The social and biophysical sciences are an important information source but are often neglected in policy and practice. The literature has identified the science, policy practice gaps as significant barriers to sustainable management of coastal resources. However, there is lack of research specifically covering the interactions between the three domains. This paper aims to: a) review the literature to identify gaps and related factors or themes contributing to the science-policy-practice disconnect; and b) propose a conceptual integrated model to address those gaps and to increase the uptake of science into policy and practice in coastal systems. The results confirm that there are gaps in the two way-links between science and policy and practice. Most research (64%) is published in the science to policy area, 32% in the policy and practice area, and only four % of the research is published in the science-policy-practice area. Effective integration is inhibited by issues of knowledge, uncertainty, communication, political and cultural issues and institutions or rules and a clear mechanism for linking science, policy and practice is needed. Frameworks may help alleviate the problem but may not be holistic or flexible enough to facilitate interactions across science-policy-practice. There needs to be a clear mechanism for integrating science, policy and practice. To address this a conceptual model of the interactions between science and policy and practice is proposed. The model includes two-way connections between science-policy-practice, mediated by both internal and external factors including key drivers, facilitators, inhibitors and barriers. The model is applied to three case studies, namely: implementing international level blue carbon policy at a local level; an historical perspective on mangrove damage and restoration at an Australian state level; and an Australian example of long-term interactions between science, policy and practice, illustrating how multiple connections and interactions can occur as projects proceed. Highlights: There is a lack of connection between science, policy and practice. Issues include knowledge, uncertainty, communication, politics, institutions. A conceptual model was developed linking science policy and practice. The model was applied to case studies from an international to a local scale.